Agreement, case and locality in the nominal and verbal domains - Marchis Moreno, Mihaela; Reeve, Matthew (Open Generative Syntax, 2019)
This book explores the Agree operation and its morphological realisations (agreement and case), specifically focusing on the connection between Agree and other syntactic dependencies such as movement, binding and control. The chapters in this volume examine a diverse set of cross-linguistic phenomena involving agreement and case from a variety of theoretical perspectives, with a view to elucidating the nature of the abstract operations that underlie them. The phenomena discussed include backward control, passivisation, progressive aspectual constructions, extraction from nominals, possessives, relative clauses and the phasal status of PPs.